PENDIDIKAN DALAM PERSPEKTIF AL-QURAN - Subhan, Mohammad (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract : When mankind is born, they  have been endowed with the basic skills, physical and spiritual which will be developed through education. Without education, these  potentials  cannot develop optimally. Thus, education is  conditio sine quanon to develop human potentials to create human beings who are ready to serve God, becoming  caliph on Gods mandate, and to realize the joy of living in the world and the hereafter. To achieve these objectives, the development of human potentials through education must be based on quranic values.